SHEAR BOND STRENGTH BRACKET METAL DENGAN BAHAN ADHESIF CHEMICALLY CURED DAN LIGHT CURED YANG TERKONTAMINASI SALIVA TERHADAP EMAIL - Iin Sundari; Rafinus Arifin; Rita Maulida (Journal of Syiah Kuala Dentistry Society, 2017)
The used of orthodontic brackets was to correction the function of mastication and aesthetic. Orthodontics bracket needed an adhesive material to bonding to enamel. Adhesives materials growth very wide to improved the bonding of bracket to enamel. In this study used two kind of adhesives material based on the polymerization, chemically cured bonding material and light cured bonding material. The risk of salivary contamination can lead to bonding failure. The aimed of this study was to get information about the shear bond strength of metal brackets using chemically cured adhesive and cured light adhesive contaminated saliva. Twenty extracted human premolars were randomly divided into two groups of 10 each (n=10). In group I, was used with chemically cured adhesive contaminated saliva. In group II, was used with light cured adhesive contaminated saliva. Shared bond strength test used Universal Testing Machine (UTM) with force 200 kgf and crosshead speed 0.5 mm/minute. The data was analyzed by using unpaired t test. The result showed that there were no significant differences in the shear bond strength of metal brackets using chemically cured adhesive and cured light adhesive contaminated saliva (p0,05). The conclusion of the study is no differences in the shear bond strength of metal brackets using chemically cured adhesive and cured light adhesive contaminated saliva.Keyword: shear bond strength, chemically cured adhesive, light cured adhesive, contaminated saliva